Above and Below Ground Competition for Resources in a Sesbania and Maize Agroforestry System (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted at ICRAF Field Research Station inMachakos, Kenya. It was designed to determine the relative importanceof above and below ground competition between three sesbanias(Sesbania goetzei, Sesbania macrantha, and Sesbania sesban) and maize(Zea mays). To separate above and below ground competition, guy wiringand root barrier were used to remove shade and root competition,respectively, for each of the Sesbania species. Free growth, where bothroots and shade are present, was also used for each species. Sole maizewas used as control. The treatments were arranged in a randomizedcomplete block design with three replications. The three Sesbania specieswere intercropped with maize; one row of trees followed by seven rows ofmaize in each plot. Yield components of maize and light interceptionwere monitored for four months. The results indicated that both S.macrantha and S. sesban negatively affected maize growth and yield.Maize height and yield increased with distance from the trees.
Keywords: Agroforestry; interactions; competition; grain yield; light interception